Metallaphotoredox-catalyzed C–H activation: regio-selective annulation of allenes with benzamide. Issue 5 (7th January 2021) - Li, Tianlei; Li, Jishun; Zhu, Zihao; Chen, Yuyuan; Li, Xueyao; Yang, Qingyun; Xia, Jie; Zhang, Wenxuan; Zhang, Chao; Pan, Weidong; Wu, Song
Abstract : We have developed an efficient annulation of benzamides with allenes using cobalt and photoredox dual catalysis under an oxygen atmosphere. The transformation features an alternative strategy for the regeneration of a cobalt catalyst with the aid of Eosin Y. Abstract : We have developed an efficient annulation of benzamides with allenes using cobalt and photoredox dual catalysis under an oxygen atmosphere. This reaction provides a mild and environmentally friendly method for the construction of isoquinolinone scaffolds in good to excellent yields, demonstrating broad substrate scopes, high regioselectivity, and good functional group compatibility. Notably, the transformation features an alternative strategy for the regeneration of a cobalt catalyst with the aid of Eosin Y. Preliminary mechanistic studies reveal that a radical-mediated cascade annulation is involved in this reaction.